Mass Emigration and the Erosion of Liberal Democracy - Daniel Auer; Max Schaub (International Studies Quarterly, 2024)
In many regions of the world, liberal politics is on the retreat. This development is usually explained with reference to inherently political phenomena. We propose an alternative explanation, linking democratic backsliding to deep-reaching demographic change caused by mass emigration. We argue that because migrants tend to be more politically liberal, their departure, if quantitatively significant, can hurt liberal democracy. Empirically, we focus on Central and Eastern Europe (CEE). Since 2004, the region has lost about 9 percent of its population due to migration to Western Europe. Drawing on data from 430,000 individuals and a panel analysis, we show that CEE migrants systematically hold more liberal values than non-migrants and that their exit went along with a deterioration of democracy in their home countries. Further analyses show that the mechanism we describe generalizes to various other world regions. Mass emigration may pose a challenge to democratic development in migrant-sending countries around the globe.
https://doi.org/10.7910/DVN/DLJ33W
Keywords: 320